A framework for development of model-driven decision support system / Mohd Razilan Abdul Kadir ... [et al.] - Abdul Kadir, Mohd Razilan; Md.Daud, Ruzaif Adli; AH, Juwahir; Saaid, Fatimah Almah (Faculty of Information Management, 2005)
With expansion and growth in computing technology, systems for supporting decision-makers in planning can be crucial, either to expedite and enhance the work environment or to gain efficient and effective forecasting results, as to compete with other rivals in business war-gaming. In this article, we will explore the state-of-art in developing a Model- Driven Decision Support System (DSS) namely Forecasting Support Systems (FSS), via time series forecasting model which based on Box- Jenkins approach known as ARIMA, as the analytic model in model base; for managerial and executive level, dominantly who involves inforecasting field. The aim of this paper to discuss on how decision-making process (with respect to forecasting and planning) can have its computerized support by a DSS, also to understand the concepts of FSS component and its development via DSS technology levels, which may support managers in decision making process, emphasizing on concept and approach of Box-Jenkins.